A study on the search area detection algorithm for car license plate extraction; The 1st International Conference on Information Technology, november 28-30, Suwon, Korea, 2003 - Lee Jongmin; Ha Dongmun; Alkhimov Yu. V. Yuri Vasilyevich; Kim Yongdeak (2003, 2003)
В фонде НТБ ТПУ отсутствует